Quantification of Viral RNA and DNA Positive Cells in Tissues From Simian Immunodeficiency Virus/Simian Human Immunodeficiency Virus Infected Controller and Progressor Rhesus Macaques - Pahar, Bapi; Kuebler, Dot; Rasmussen, Terri; Wang, Xiaolei; Srivastav, Sudesh K.; Das, Arpita; Veazey, Ronald S. (Frontiers in Microbiology, 2019)
Eradication of HIV-1 from an infected individual cannot be achieved using current antiretroviral therapy (ART) regimens. Viral reservoirs established in early infection remain unaffected by ART and are able to replenish systemic infection upon treatment interruption. Simian immuno- deficiency virus (SIV) infected macaque models are useful for studying HIV pathogenesis, treatments, and persistent viral reservoirs. Here we used the SIV macaque model to examine and quantify RNA and DNA positive cells in tissues from macaques that control viral replication (controllers) and those that have persistently high plasma viremia (progressors). A positive correlation was detected between tissue RNA+ cells and plasma viral load in both mesenteric lymph node (LN) and spleen. Similarly, a positive correlation also observed between DNA+ cells and plasma viral load in ileum and jejunum. Controllers had a lower frequency of both RNA and DNA+ cells in several tissues compared to progressors. However, DNA+ cells were prevalent in mesenteric LN, inguinal LN, colon, midbrain and bone marrow tissues in both controller and progressors. Organized lymphoid tissues of LNs, spleen and intestine were found the major tissues positive for virus. Viral RNA and DNA positive cells were detected in brain and thymus in macaques with high plasma viremia and SIV-encephalitis. Both T cells and macrophages were shown to be infected in several tissues, indicating vaccines and ART should be specifically designed to protect these cells in organized lymphoid tissues. These results indicate ART should target infected cells in secondary lymphoid organs to reduce both productively and latently infected cells.